Establishment of cell lines with increased susceptibility to EV71/CA16 by stable overexpression of SCARB2 - Li, Xiaojun (BioMed Central, 2013)
BACKGROUND: Human enterovirus type 71 (EV71) and Coxsackievirus A group type 16 (CA16) belong to human Enterovirus species A of the family Picornaviridae. These viruses are recognized as the major pathogens responsible for epidemics of hand-foot-mouth disease (HFMD), which presents with fever and vesicular eruptions of palms, soles of the feet or mouth. Human scavenger receptor class B, member 2 (SCARB2) has been identified as the receptor for both EV71 and CA16, as overexpression of SCARB2 in cells can enhance virus replication significantly. METHODS: In this study, we used a lentivirus packaging vector to transduce the SCARB2 gene into human embryonic kidney cells (293), human rhabdomyosarcoma cells (RD) and African green monkey kidney cells (Vero) to create stable expression lines. Expression of SCARB2 in the resulting three transgenic cell lines was confirmed by real-time RT-PCR, immunofluorescence and flow cytometry. RESULTS: Levels of SCARB2 mRNA determined by real-time RT-PCR in 293-SCARB2 (293S) or RD-SCARB2 (RDS) transgenic cell lines were approximately 2 × 10(2) times higher than those in 293 and RD cells, respectively, and three times higher in Vero-SCARB2 (VeroS) than in Vero cells. Furthermore, EV71 and CA16 virus titers in 293S and RDS cells were 10(2)–10(3)-fold higher (detected in RD cell) than those in the parental cells, and a 10-fold higher titer of EV71 was achieved in VeroS cells compared with that in Vero cells. CONCLUSIONS: We established for the first time three cell lines stably overexpressing SCARB2, which showed drastic increases in susceptibility to EV71/CA16 infection. These optimal cell lines may be utilized to develop inactivated vaccines for EV71/CA16 and facilitate rapid detection and isolation of HFMD pathogens or other Enterovirus serotypes. Furthermore, these stable cell lines also can serve as tools to facilitate drug screenings as well as molecular studies on virus-host interactions and pathogenesis of causative agents for HFMD.